Interspecific Differences in the Flow Regimes and Drag of North Pacific Skate Egg Cases. (4th July 2022) - Hall, Kayla C; Elcock, Jaida N; Hoff, Gerald R; Stevenson, Duane E; Summers, Adam P; Donatelli, Cassandra M
Synopsis: Skates are a diverse group of dorso-ventrally compressed cartilaginous fish found primarily in high-latitude seas. These slow-growing oviparous fish deposit their fertilized eggs into cases, which then rest on the seafloor. Developing skates remain in their cases for 1–4 years after they are deposited, meaning the abiotic characteristics of the deposition sites, such as current and substrate type, must interact with the capsule in a way to promote long residency. Egg cases are morphologically variable and can be identified to species. Both the gross morphology and the microstructures of the egg case interact with substrate to determine how well a case stays in place on a current-swept seafloor. Our study investigated the egg case hydrodynamics of eight North Pacific skate species to understand how their morphology affects their ability to stay in place. We used a flume to measure maximum current velocity, or "break-away velocity, " each egg case could withstand before being swept off the substrate and a tilt table to measure the coefficient of static friction between each case and the substrate. We also used the programing software R to calculate theoretical drag on the egg cases of each species. For all flume trials, we found the morphology of egg cases and their orientation to flow to be significantly correlated with break-away velocity. In certain species, the morphology of the egg case was correlated with flow rate required to dislodge a case from the substrate in addition to the drag experienced in both the theoretical and flume experiments. These results effectively measure how well the egg cases of different species remain stationary in a similar habitat. Parsing out attachment biases and discrepancies in flow regimes of egg cases allows us to identify where we are likely to find other elusive species nursery sites. These results will aid predictive models for locating new nursery habitats and protective policies for avoiding the destruction of these nursery sites.